Virtual vs. partial internet shopping: user perception / Hazura Ahmad Bustaman - Ahmad Bustaman, Hazura (2006)
The internet has many facets. It is a place for advertising, brokerage, communication, discussion of problems , distance learning, education, entertainment, findings partners, listening to the radio, home banking, home working, information consultancy, information resources management, international contacts, interpersonal computing, looking at pictures, market analysis, news agencies, parallel computing, pre-publishing, publishing, reading, searching, selling, shopping, and software downloading. It is the place to accustom millions of users to the information market of tomorrow. Internet shopping consists of the final activities and steps needed to place a product in hands of the ultimate customer to provide services to the customer. By shopping online, customers can buy the products or services needed via Web in anytime and anywhere. The purpose of the study is to identify the user perception toward virtual and partial internet shopping and to identify which product that user prefers to buy online whether virtual or partial products/services. This study was conducted among students in UiTM, Shah Alam, Selangor from many faculties. Through this study, there are identified five attributes of internet shopping features such as security and privacy, ease of use, convenience, service availability and guarantees and return policies. Beside that, the study also evaluates the behavioral intention of respondents to shop online. For the analyses and findings in this study; descriptive, Cronbach's Alpha of reliability test, Pearson Chi-Square Test, Normality Test, and Coefficient Correlation Test, were conducted. From the analysis it shows that five attributes of virtual and partial internet shopping are significant to respondents' perception. This study also suggests several recommendations to future researcher and to retailers in order to improve their web site features to attract and convince the users to buy online.